THE IMAGINED COMMUNITY OF INDONESIA: PERTENTANGAN NASIONALISME INDONESIA VS ETNONASIONALISME BANGSA ACEH DALAM GERAKAN ACEH MERDEKA (GAM) - Aprita Sari, Cut Maya (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
The greatest history of Aceh shows that Aceh was once a prosperous and sovereign autonomous State. On the other hand, before reaching its independence, Indonesia still consists of islands which is name Nusantara. Acehs triumphs that had never been conquered by the Dutch caught Soekarnos interest in calling for Acehs assistance in defending Indonesias independence. Sukarno also invited Aceh to join and become a part of the Republic of Indonesia and build the Nationalism through The Imagined Community Of Indonesia. After joined Indonesia, Aceh experienced various social and economic discriminations that generated ethnic sentiment through the Free Aceh Movement (GAM). The purpose of this study is to conduct a theoretical analysis of the Indonesian nationalism penetration by GAM through the use of ethnic identity. This research uses qualitative method with literature study and refers to two main theories namely Nationalism initiated by Bennedict Anderson (1991) and ethnic theory which was initiated by Anthony Smith (1981). The results of this study indicate that GAM became a massive movement because it managed to build ethnic sentiment through the use of ethnic identity and against Indonesian nationalism. On this basis GAM gained great support from its followers and sympathizers to separate from Indonesia